Development of a dry powder formulation for pulmonary delivery of azithromycin-loaded nanoparticles - Sani, Alison Tatiana Madrid (2024)
Wethank Dr. Danae Lopes Francisco for collaboration with MEVimagesandMSc.KellyCristina Manhani for the support in quantification analyses. We also grateful to pharmaceutical companies Laboratório Cristália (Brazil), Lipid Ingredients (Brazil), and DFE Pharma (Germany) for kindly providing azithromycin dehydrated, soybean lecithin S75, and lactose monohydrated LH206, respectively.